Growth dynamics of citrus fruits in India: A decomposition analysis with seasonal indicators - SHARMA, VARNIKA; THAKUR, VISHANI; CHANDEL, ASHU; GUPTA, R K; SAMRITI; GUPTA, VIJIT (The Indian Journal of Agricultural Sciences, 2026)
This study focused on the dynamics of citrus production in India and Himachal Pradesh over a 48-year period (1975–2022), emphasizing regional differences and underlying development drivers. Compound annual growth rate (CAGR) and decomposition analysis were employed to examine the contributions of acreage, yield and their interaction to production growth. Citrus production in India was primarily area-driven, with acreage growing by 12.96% during the period, while yield gains were minor (-0.26%). In Himachal Pradesh, however, output growth was driven by yields, with an 8.11% increase contributing considerably to the overall 10.45% growth. Seasonal indices of lemon prices and arrivals in four main North Indian markets Ambala, Jassur, Azadpur and Dehradun showed that prices peaked in april and may, with arrivals following similar seasonal trends. Notably, Azadpur had the highest price trend value of 7.73 in December, demonstrating the impact of large-scale production and effective supply chains. This study emphasises the importance of yield improvements, as evidenced by Himachal Pradesh’s success, and highlights the necessity for targeted interventions to overcome yield stagnation in India. It underscored the relevance of contemporary farming techniques, resource management, and climate-friendly solutions for increasing productivity. Furthermore, insights about lemon market trends provided actionable guidance for optimising supply chains and eliminating market anomalies, particularly in volatile places such as Ambala and Dehradun. By combining data analysis with policy recommendations, this paper provides a comprehensive framework for enhancing citrus production and market efficiency in India.